MULTI-CHANNEL TRADE INFLUENCE IN THE LOGISTICS RESEARCH CONTEXT - Fursa, Viktoria; Larina, Tetiana; Danylenko, Valerii (Social Economics, 2020)
The study presents in general terms the changes and trends that have emerged in the last decade and concern sales model implementation in companies operating on the Ukrainian consumer market. The presented trends influence on the above-mentioned entities` behavior model from the perspective of using certain operational and strategic management tools is analyzed. The reasons for shifting priorities in the relations development within the structure of vertically integrated and vertically located entities with an eye to the realities of the consumer market new paradigm are indicated. The demand development features in the new conditions and changes that have occurred in the consumers` actions, as well as the accompanying prospects for the development of the consumer-expected competencies of the seller are highlighted. The facts of brand-new marketing and logistics practice dissemination are presented. This is about such a modern method of implementing sales competencies as sales through multi-channel retail networks and supply chains. The influence of new logistics and marketing tools on the nature of competitive relations within the studied market boundaries is also described. The reasons for the need to include new trade relations development trends in the program of scientific and methodological development of logistics and marketing strategies are revealed. As a result, the necessity of performing the conceptual and categorical apparatus synthesis for further research of e-Commerce practice is revealed and indicated. Based on the results obtained at the current stage, a system of indicators was established in order to identify the differences between the traditional single-channel sales methodology and the features of multi-channel supply chain management. When developing this system, it was decided to divide the indicators by their functional characteristics. To achieve the goal set in this study, the selection of indicators was focused on the logistics component of single- and multi-channel supply chains. The resulting indicators system was used to perform a comparative analysis of the mentioned supply chains. Along with the direct results presented in the manuscript, the analysis allowed us to describe in general terms the differences between traditional stationary retail trade and trade using information technology tools. Among other things, the analysis of scientific sources on this topic allowed us to come to some conclusions about the advantages of using multi-channel sales systems.